On keeping the right ER size - Schuck, Sebastian (Nature cell biology, 2016)
The endoplasmic reticulum (ER) is the largest membrane-bound organelle in cells, and its size needs to be carefully controlled. Downsizing the ER by autophagy is now shown to involve Sec62, a protein that also helps to build up the organelle. This link suggests a molecular switch for ER size control.
Gesehen am 26.05.2020